Pengaruh Kepemimpinan Kepala Sekolah Terhadap Kepuasan Kerja Guru SD Se-Kecamatan Dua Boccoe Kabupaten Bone - Lidiya, Lidiya; Faisal, Muhammad; Wahira, Wahira (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2025)
This study is an ex post-facto research  that aims to find out whether there is an influence of school principal's leadership on the job satisfaction of elementary school teachers in Dua Boccoe District. The independent variable in this study is the leadership of the principal, while the bound variable is the job satisfaction of elementary school teachers in Dua Boccoe District. The population in this study is all school teachers in Dua Boccoe District, while the sample is elementary school teachers in Dua Boccoe District spread across 17 schools totaling 35 teachers. The data of the research results was obtained by distributing written questionnaires in the form of questionnaires. Data analysis techniques in quantitative research use statistics, namely descriptive statistics and inferential statistics. The results of the study show that  the leadership of elementary school principals in Dua Boccoe District is in the medium category and the job satisfaction of elementary school teachers in Dua Boccoe District is in the medium category. In addition to the influence of leadership, the principal makes a great contribution to the job satisfaction of teachers, in addition to other influencing factors.